High Characteristic Temperature InGaAsP/InP Tunnel Injection Multiple-Quantum-Well Lasers - 汪洋 邱应平 潘教青 赵玲娟 朱洪亮 王圩 (Chinese physics letters, 2010)
We fabricate 1.5 μm InGaAsP/InP tunnel injection multiple？quantum-well （TI-MQW） Fabry-Perot （F-P） ridge lasers. The laser heterostructures, including an inner cladding layer and an InP tunnel barrier layer, are grown by metal-organic chemical-vapor deposition （MOCVD）. Characteristic temperature T0 of 160 K at 20°C is obtained for 500？μm？long lasers. T0 is measured as high as 88 K in the temperature range of 15？75°C. Cavity length dependence of T0 is investigated.